Special Component Plan 1994-95 Proposals - Planning Commission (Planning Commission, 1994)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanem lying geographically isolate- from one another. Pondicherry region which is on the east coast, about 162 kms. south of Madras is the largest of these and consists of 12 scattered areas interspersed with enclaves of South Area District of Tamil Nadu. Kareikal region is about 15C Kms. south of Pondicherry and it is surrounded by Thanjavur District of Tamil Nadu. Yanam region is located about 84C kms. north east of Pondicherry near Kakinada in Andhra Pradesh. Mahe region lies almost parallel to Pondicherry 653 kms. away on the west coast near Tellicherry in Kerala. EOPULATION: 2.The Union Territory of Pondicherry is 492 sq. kms. in area and has e population of 8/07,785 according to the 1991 census consisting of 4,68,681 males and 3,99,704 females.
Government of Pondicherry Planning and Research Department